Is it appropriate when the Heart Team changes the decision regarding the modality of myocardial revascularization? - Veljković, Stefan; Milošević, Maja; Ostojić, Miodrag; Bošković, Srdjan; Nikolić, Aleksandra; Bojić, Milovan; Otašević, Petar (Vojnosanitetski pregled, 2021)
Background/Aim. Decision-making by the Heart Team is an established way of making appropriate decisions regarding the management of patients with coronary artery disease. In clinical practice, it is not infrequent to see changes in decisions made by different Heart Teams. However, clinical implications regarding changes in the Heart Team decisions are not clear. The aim of this study was to determine clinical implications of change in the Heart Team decision in patients in whom surgical myocardial revascularization was advised first but consequently changed to percutaneous coronary intervention (PCI). Methods. We retrospectively analyzed data for 1,501 patients admitted to a single tertiary care high-volume center for coronary artery bypass grafting (CABG). In all patients, decisions were made by the Heart Team prior to admission. Upon admission, decisions were reevaluated by another Heart Team. The decision regarding the mode of revascularization was changed in 73 (4.86%) of patients. Propensity matching was made with patients from the same population who underwent CABG. Patients in both groups were followed for major adverse cardiac events (MACE) and total mortality for 12 months. Results. PCI and CABG groups were balanced with respect to demographic and clinical characteristics. All patients had two- and three vessel disease, with similar incidence of left main stenosis (26% in the PCI group and 30.10% in the CABG group). EuroSCORE II was similar between the groups (2.48 ± 2.38 vs. 2.36 ± 2.92). During the follow-up period, a total of 5 (6.80%) MACE in the PCI group and 12 (5.80%) MACE in the CABG group were observed (log rank 0.096, p = 0.757). A total of 6 (8.20%) patients died in the PCI group, and 15 (7.30%) patients died in the CABG group (log rank 0.067, p = 0.796). Conclusion. Our data indicate that patients in whom CABG was advised first but consequently changed to PCI have a prognosis similar to CABG patients over 12 months after the index procedure.